PROFIT FROM CHICKEN LIVESTOCK AGRIBUSINESS (THE TYPE OF LAYERS THAT WERE CULTIVATED AS BROILER) - Kalangi, Jolanda (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2024)
Chicken livestock business, especially roosters laying type (which was cultivated as broiler) was one of the businesses that has recently been carried out by farmers or entrepreneurs in Kawangkoan District. This chicken business has good prospects in the future, considering that the demand for chicken meat continues to grow in line with increased income and population as well as knowledge about fulfilling nutrition for families. The chicken business had not been developed with an agribusiness concept. The concept of agribusiness was a concept that refers to overall activities from upstream to downstream which consists of 4 subsystems namely agroinput, agroproduction, agroindustry, agrocommerce and agroservices subsystems. The problem was the extent to which the agribusiness system was implemented by the chicken farmer. The research method was a survey method with a case study approach. The location of the farm, namely Kayuuwi Village, was determined by purposive sampling with the consideration that the village had a rooster company the laying type which was cultivated as broiler. Respondents in the study as the owner of the company, namely Mr. Reky. The analytical method used was descriptive and profit analysis. The results showed that the production process of rooster business, laying type, was carried out 4-5 periods each year. The profit obtained during the study for 4 periods per year was IDR 21.390.000,00. Based on the results of the study it can be concluded that the laying type of rooster agribusiness was feasible to develop in terms of the RC value ratio was greater than one.